2019 International Conference on Biometrics (ICB) 2019
DOI: 10.1109/icb45273.2019.8987245
|View full text |Cite
|
Sign up to set email alerts
|

Gender Classification from Iris Texture Images Using a New Set of Binary Statistical Image Features

Abstract: Soft biometric information such as gender can contribute to many applications like as identification and security. This paper explores the use of a Binary Statistical Features (BSIF) algorithm for classifying gender from iris texture images captured with NIR sensors. It uses the same pipeline for iris recognition systems consisting of iris segmentation, normalisation and then classification. Experiments show that applying BSIF is not straightforward since it can create artificial textures causing misclassifica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…They concluded that combining the best aspects of the iris‐code from the left and right eyes resulted in an 89% reliable gender predictor. Later, Tapia and Arellano (2019) proposed a modified‐binary statistical features (MBSIF) method for gender classification and attained 94.6 and 91.33% for the left and right eye, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…They concluded that combining the best aspects of the iris‐code from the left and right eyes resulted in an 89% reliable gender predictor. Later, Tapia and Arellano (2019) proposed a modified‐binary statistical features (MBSIF) method for gender classification and attained 94.6 and 91.33% for the left and right eye, respectively.…”
Section: Introductionmentioning
confidence: 99%